STAKEHOLDERS’ PERCEPTION ON THE USE OF ELECTRONIC-PROCESSES AT UNIVERSITIES IN RIVERS STATE, NIGERIA - Ukpere, Wilfred (Annals of Spiru Haret University. Economic Series, 2020)
The use of electronic (E) processes in the workplace has become pervasive in many countries in recent years. In Nigeria the pervasive use of information technology is quite new. The adoption of this new technology is gaining momentum at Universities in Nigeria. Concepts as E-Senate, E-Campus, E-Examinations, among others depict the extent to which Universities are adopting E-processes. To drive the processes, investments in hard and soft wares are being executed with huge sums of money. This is done in the belief that the new ethos is cost effective, modern and competitive. But as an innovation, the e-processes are new and will be driven by stakeholders. These stakeholders include Management, Staff and Students; their views, reactions and actions are key determinants of its sustainability. This work is a study of stakeholders’ responses to the use of e-processes (using Rogers’ Diffusion of Innovation Theory) for service delivery by Universities in Nigeria. The outcomes of the research show that about 32 percent of staff members are fully compliant and another 55 percent are concerting efforts to achieve compliance. In all, 87 percent of those interviewed have keyed into the process. Only about 13 percent are yet to key in, these may be seen as Laggards using Rogers categorization. Since, the new process has taken off, there is need to perfect it by resolving the problems of power supply, internet access, accessories, among others that are limiting its success rate.